Answer:
Explanation:
1. Given the integral function
, using trigonometric substitution, the substitution that will be most helpful in this case is substituting x as
i.e
.
All integrals in the form
are always evaluated using the substitute given where 'a' is any constant.
From the given integral,
where a = 7 in this case.
The substitute will therefore be
![x = 7 sin\theta](https://img.qammunity.org/2021/formulas/mathematics/college/wfp0mtjgbt5nfgwol7s6evl465xgtx4m16.png)
2.) Given
![x = 7 sin\theta](https://img.qammunity.org/2021/formulas/mathematics/college/wfp0mtjgbt5nfgwol7s6evl465xgtx4m16.png)
![(dx)/(d \theta) = 7cos \theta](https://img.qammunity.org/2021/formulas/mathematics/college/twlc3a1jgzbhah586jaxfxwge9m5l7w9zz.png)
cross multiplying
![dx = 7cos\theta d\theta](https://img.qammunity.org/2021/formulas/mathematics/college/h9yyw8grc82glqoghapchlwuta1343tq2a.png)
3.) Rewriting the given integral using the substiution will result into;
![\int\limits {7\sqrt{49-x^(2) } } \, dx \\= \int\limits {7\sqrt{7^(2) -x^(2) } } \, dx\\= \int\limits {7\sqrt{7^(2) -(7sin\theta)^(2) } } \, dx\\= \int\limits {7\sqrt{7^(2) -49sin^(2)\theta } } \, dx\\= \int\limits {7\sqrt{49(1-sin^(2)\theta)} } } \, dx\\= \int\limits {7\sqrt{49(cos^(2)\theta)} } } \, dx\\since\ dx = 7cos\theta d\theta\\= \int\limits {7\sqrt{49(cos^(2)\theta)} } } \, 7cos\theta d\theta\\= \int\limits {7\{7(cos\theta)} }}} \, 7cos\theta d\theta\\](https://img.qammunity.org/2021/formulas/mathematics/college/t0juaw6vgzh87c33q973jgxr9ez05b0l8w.png)
![= \int\limits343 cos^(2) \theta \, d\theta](https://img.qammunity.org/2021/formulas/mathematics/college/bp82wm8nivp8tbpzhzn8ncf6bnvz6ohbe9.png)